2003
DOI: 10.1007/s00223-002-2052-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover Responses to Changed Physical Activity

Abstract: The aim of the study was to compare bone turnover in male soccer players with controls and to follow bone turnover with changes in activity level. Serum-osteocalcin (OC), carboxy-terminal propeptide of type I collagen (PICP) and total alkaline phosphatases (tALP) were measured to assess bone formation. Bone resorption was detected by carboxyterminal cross-linked telopeptide of type I collagen (ICTP). Bone turnover of 12 male premier league soccer players (mean age 23 years, range, 17-34) exercising 12 hours/we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 37 publications
1
29
1
Order By: Relevance
“…High physical activity as reported by patients has been reported to be associated with high BMD in healthy individuals (44,45). The effects of physical activity on bone turnover are well known (46,47). The finding that self-reported leisure time physical activity did not correlate to bone mineral density measurements or markers of bone turnover in this study may indicate that this subjective estimation fails adequately to reflect the physical activity of these patients.…”
Section: Discussionmentioning
confidence: 54%
“…High physical activity as reported by patients has been reported to be associated with high BMD in healthy individuals (44,45). The effects of physical activity on bone turnover are well known (46,47). The finding that self-reported leisure time physical activity did not correlate to bone mineral density measurements or markers of bone turnover in this study may indicate that this subjective estimation fails adequately to reflect the physical activity of these patients.…”
Section: Discussionmentioning
confidence: 54%
“…Aerobic exercise such as long-distance running (42) or brisk walking (45) also lowers the concentrations of bone formation markers. However, the comparison of our results with other work is difficult because most previous studies analyzed training effects or compared different physical activity levels on bone metabolism (48)(49)(50). Obviously, a single session of exercise may have different effects on bone than regular exercise over a long period.…”
Section: Discussionmentioning
confidence: 61%
“…This excess weight has a deleterious effect upon general locomotion and soccer-specific actions such as jumping to contest aerial possession of the ball. The fat-free compartment, which includes lean muscle mass and bone mineral mass, is important for the production of speed, strength and power, and for injury prevention (Arden & Spector, 1997;Karlsson et al, 2003). It has been reported that elite soccer players demonstrate greater bone and lean mass and lower body fat values than their non-soccer counterparts (Calbet, Dorado, Díaz-Herrera, & Rodríguez-Rodríguez, 2001;Wittich, Oliveri, Rotemberg, & Mautalen, 2001).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%